GE_GERICHTE C/11551/2007 vom 29. November 2007 - GE Cour de justice (2007)
; MAINLEVÉE DÉFINITIVE ; DETTE ALIMENTAIRE ; COMPENSATIO ; SUSPENSION DE LA PROCÉDURE | LP.80. LP.81. CO.125.2. LPC.107. LPC.306A